An Analysis of the Implementation of the Almsgiving Program as a Philanthropic Practice to Shape Students’ Social Awareness - Nuris Syamsiyah; Abd. Mannan; Siti Fatima (Seutia Hukamaa Cendekia, 2026)
This study aims to analyze the implementation of the charity program as a philanthropic practice in shaping students' social awareness at SD Negeri Gunung Sekar 1, Sampang. This research is motivated by the importance of developing a caring social character among elementary school students amid declining empathy and social concern in children. The study uses a qualitative, phenomenological approach to understand students' experiences and perceptions of charity activities conducted within the school environment. The research subjects include the principal, Islamic Religious Education teachers, homeroom teachers, and students from grades 4 to 6. Data collection was carried out through in-depth interviews, observations, and documentation. The results show that charity activities are carried out regularly through the Jum'at Religi program, which involves all students in sharing activities and other social activities. The practice of charity is not only a religious activity but also a means of fostering social habits that cultivate empathy, sharing, and helping behaviors among students. Direct experience in charity activities helps students understand charity as both an act of worship and a form of concern for others. Additionally, charitable activities play a role in building a culture of social awareness within the school environment, resulting in better social relationships among students and increased concern for others